Regional Public Service Agency’s Financial Management Implementation in Walanda Maramis North Minahasa Public Hospital - Freddy Semuel Kawatu; Cecilia Lelly Kewo (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
Regional Public Service Agency’s Financial Management is one of the new policies from government in order to improve financial performances and public services at Walanda Maramis North Minahasa Public Hospital. The purpose of this research is to analyze Regional Public Service Agency’s Financial Management in Walanda Maramis North Minahasa Public Hospital (before and after implementing). This research uses qualitative approach with descriptive analyze method; secondary data sources from 2020 and 2021 financial reports, journal articles, reference books and interview instruments. Balanced Scorecard and Model Analyze by Miles and Huberman is the analyzing technic used to comprehensively measure the financial and non-financial performances. Result of this research shown: 1) Walanda Maramis North Minahasa Public Hospital had implementing financial management of Regional Public Service Agency in forms of governances, accountabilities and transparency; and 2) performances evaluations is consist of three aspects, financial performance, operational services performance, and service quality improvement performance, which contributing to the public’s services and welfare, which also got Healthy grade financial performance with 74.15 score. Keywords: Implementation, Financial Performances, Regional Public Service Agency